INCORPORATING PROJECT-BASED LEARNING (PBL) INTO A UNIVERSITY SPEAKING CLASSROOM: WHY AND HOW? - Wisma Yunita (BASIS (Bahasa dan Sastra Inggris), 2015)
Learning a language means learning thelanguage knowledge (vocabulary and grammar) and the language skills (reading, listening, speaking and writing). Of all the four skills, speaking skill is considered to be the most favourite and challenging one.It contains a complex process of constructing meaning and requires the language learners to produce linguistically and pragmatically correct utterances. To achieve such goals, a teacher who teaches speaking skills especially at a university level classroom should use a meaningful, appropriate and a challenging teaching method or technique. One of the methods that attract many language teachers’ interests currently is project-based learning. Project-based learning is a teaching method in which the students gains knowledge and skills byworking for an extended period of time to investigate and respond to a complex question, problem, or challenge. It empowers learners to pursue content knowledge on their own and demonstrate their new understandings through a variety of presentation modes. In this paper, the writer will discuss about speaking skill, teaching speaking skill, project-based learning definitions, characteristics and its steps, the reasons why English teachers especially at universities should incorporate project-based learning into a speaking classroom and an example on how to incorporate the project-based learning into a university speaking classroom.